Letter from Clark Wissler to Major Otto William Geist, Quartermaster - Wissler, Clark, 1870-1947 (1946)
This archival material has been provided for educational purposes. Ball State University Libraries recognizes that some historic items may include offensive content. Our statement regarding objectionable content is available at: https://dmr.bsu.edu/digital/about